Design of a New Type of SEA Structure and Optimization of Elastic Elements - Li Yuqing; Liu Ning (Jixie chuandong)
In order to meet the motion requirements of the elbow joint of the rehabilitation robot, a double-node symmetrical spiral corrugated elastic element is applied to the series elastic actuator (SEA), and the energy storage ratio is used as the optimization standard. Under the premise of the same quality,the maximum energy storage ratio can be achieved, which can better absorb the vibration of the mechanical arm and ensure the safety of the patient. Firstly, the three-dimensional modeling of the SEA is carried out. Then the torque spring is simulated and analyzed by using the finite element software, and the safety factor of the elastic unit is 2.37. Finally, the real object is processed. The experiment shows that the energy storage ratio can reach 9.63 J/kg, the measured stiffness kr is 264.04 N<alternatives>∙ <?fx-imagestate width="1.86266661" height="2.62466669"?> <?fx-imagestate width="1.86266661" height="2.62466669"?> </alternatives>m/rad, the error of the simulated stiffness is 6.86%, and the torsion angle and torque of the elastic unit are linear and can be used for the flexible connection of the robotic arm, which lays the foundation for the further optimization of the robot, and also provides a technical verification method for solving such problems.